Type 2 Diabetes From Pathophysiology to Modern Management - Siderova, Mira (IntechOpen, 2019)
The emergence of type 2 diabetes as a global pandemic is one of the major challenges to health care in the 21st century. This book contains chapters covering the newest scientific concepts in the pathogenesis of type 2 diabetes, and the complications and approaches in diagnosis and glycemic control. Part of the book is dedicated to the effect of diabetes on the mental functions and treatment strategies to prevent cognitive decline. Glucose monitoring, using cutting-edge technologies, is outlined, as well as the role of health information technologies in diabetes management. Updates on glucose lowering therapy are presented, and the new emerging class of SGLT2 inhibitors is discussed in detail. The purpose of this book is to disseminate knowledge on type 2 diabetes and to contribute to the professional development of physicians, internists, endocrinologists, medical students, and research scientists in diabetes.